2008
DOI: 10.1586/14737175.8.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for social anxiety disorder: a systematic review

Abstract: Social anxiety disorder (SAD) is a prevalent, disabling disorder. We aimed to assess the effects of pharmacotherapy for SAD and to determine whether particular classes of medication are more effective and/or better tolerated than others. A systematic review and meta-analysis was conducted of all published and unpublished placebo-controlled randomized controlled trials (RCTs) undertaken between 1966 and 2007. A rigorous search, which included searching the Cochrane CCDANTR, MEDLINE and PsycINFO electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 107 publications
0
28
1
Order By: Relevance
“…As the average placebo response rate across randomized controlled trials in SAD has been reported to be approximately 30% (Ipser et al, 2008), the measured differential brain activity associated with treatment response in the present study could reflect a combination of medication and expectancy/ placebo responses inherent to the open pharmacotherapy trial. This limitation may be mitigated partially by the fact that the pre-to posttreatment midline vmPFC finding observed in the present study is anatomically distinct from a common mediating anatomy that has been observed for placebo responses in pain, depression, and anxiety (eg dorsolateral/ventrolateral PFC, rostral and dorsal ACC) (Mayberg et al, 2002;Benedetti et al, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…As the average placebo response rate across randomized controlled trials in SAD has been reported to be approximately 30% (Ipser et al, 2008), the measured differential brain activity associated with treatment response in the present study could reflect a combination of medication and expectancy/ placebo responses inherent to the open pharmacotherapy trial. This limitation may be mitigated partially by the fact that the pre-to posttreatment midline vmPFC finding observed in the present study is anatomically distinct from a common mediating anatomy that has been observed for placebo responses in pain, depression, and anxiety (eg dorsolateral/ventrolateral PFC, rostral and dorsal ACC) (Mayberg et al, 2002;Benedetti et al, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…2,3 Early onset of the disorder often results in a chronic course and functional disability. 4 Although both pharmacotherapy and psychotherapy are reportedly effective for social anxiety, 5,6 studies indicate that only about half of people with social anxiety ever seek treatment. 7 The disorder-specific fear of meeting a therapist may prevent them from seeking counseling from mental health professionals.…”
mentioning
confidence: 99%
“…Several longterm studies (double-blind and open-label) have been conducted to examine the issue of relapse prevention. [13] These studies have evaluated moclobemide, phenelzine and CBT, sertraline and exposure therapy, fluvoxamine, paroxetine and escitalopram and venlafaxine ER. Response rates in these studies range from 58% for venlafaxine ER to 88% for escitalopram.…”
Section: Maintenance Treatmentmentioning
confidence: 99%